Mengintegrasikan Matematika dan Budaya Berbasis Pembelajaran Kontekstual:Studi Kasus Penghitungan Skala dan Jarak pada Ziarah ke Makam Gus Dur di Sekolah Dasar - Refi Mariska; Muhammad Affan Habibie; Rizqiyatul Khasanah (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Contextual approach is a learning approach that correlates material with real life. There are many ways that are applied in contextual learning, one of them with learning activities outside or tourism works. This study aims to integrate the activities of pilgrimage to the grave of Gus Dur in learning mathematics can help students in grade 5 elementary school understand the concept of scale and distance more effectively. This case study is expected to provide insight into the benefits of combining local wisdom in the mathematics curriculum, as well as enriching teaching methods in elementary schools. This research is a qualitative study through a survey approach and literature study. The sample in this study was 30 students at the 5th grade level at SD Negeri 6 Kedungwuni Pekalongan Regency. Data collection techniques used by researchers are, using interviews with students and teachers. The results showed that tourism work activities can increase students' understanding and enthusiasm in understanding mathematical concepts.